Experimental Models of Maternal Obesity and Neuroendocrine Programming of Metabolic Disorders in Offspring - Reynolds, Clare M.; Segovia, Stephanie A.; Vickers, Mark H. (Frontiers in Endocrinology, 2017)
Evidence from epidemiological, clinical and experimental studies have clearly shown that disease risk in later life is increased following a poor early life environment, a process preferentially termed developmental programming. In particular, this work clearly highlights the importance of the nutritional environment during early development with alterations in maternal nutrition, including both under- and overnutrition, increasing the risk for a range of cardiometabolic and neurobehavioral disorders in adult offspring characterised by both adipokine resistance and obesity. Although the mechanistic basis for such developmental programming is not yet fully defined, a common feature derived from experimental animal models is that of alterations in the wiring of the neuroendocrine pathways that control energy balance and appetite regulation during early stages of developmental plasticity. The adipokine leptin has also received significant attention with clear experimental evidence that normal regulation of leptin levels during the early life period is critical for the normal development of tissues and related signaling pathways that are involved in metabolic and cardiovascular homeostasis. There is also increasing evidence that alterations in the epigenome and other underlying mechanisms including an altered gut-brain axis may contribute to lasting cardiometabolic dysfunction in offspring. Ongoing studies that further define the mechanisms between these associations will allow for identification of early risk markers and implementation of strategies around interventions that will have obvious beneficial implications in breaking a programmed transgenerational cycle of metabolic disorders.